PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT. KERTAS TRIMITRA MANDIRI BANDUNG - Fransiska Wuri Wulandari; Nur Azizah; Sophia Rahmi; Kunto Ajibroto (STIE Trisna Negara OKU Timur, 2023)
This study aims to determine whether there is influence of work environment and work stress on employee performance at PT. Paper Trimitra Mandiri Bandung. The problems studied in this study are related to the presence of high environmental factors and work stress on employee performance. The research method used is descriptive verification method with a quantitative approach using path analysis (Path Analysis), because this research besides wanting to get an overview of employee performance associated with the work environment and work stress, also get a picture of the pattern of relationships and the influence of variables established research.The results of the study, in general, the effect of the work environment and work stress on employee performance at PT. Paper Trimitra Mandiri Bandung and the highest influence on employee performance and work stress variable on employee performance is moderate. The simultaneous influence of work environment and work stress on the performance of fatigued employees is high, meanwhile . From the results of the research conducted, the work environment and work stress variables when combined will have a significant influence on the performance of employees of PT. Paper Trimitra Mandiri Bandung.